1999
DOI: 10.1590/1809-43921999293445
|View full text |Cite
|
Sign up to set email alerts
|

Conservação de palmito de pupunha em atmosfera modificada1

Abstract: RESUMO -O mercado do palmito de pupunha (Bactris gasipaes) está expandindo rapidamente no Brasil e diferenciando-se com a inclusão do palmito fresco ou minimamente processado. Devido sua alta perecibilidade, a conservação desse palmito fresco é difícil e requer estudos de conservação em refrigeração aliada à atmosfera modificada. As qualidades sensoriais do palmito fresco foram avaliadas ao longo de sua conservação sob refrigeração, em sacos de polietileno, com e sem absorvente de oxigênio. A textura, crispide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…The fruit is an excellent food, with starches, lipids, carotene and all essential amino acids (Yuyama et al 2003). The heart-of-palm is composed of unexpanded juvenile leaves and subapical tissue, and has low concentrations of peroxidases and polyphenoloxidase, allowing in natura commercialization, as well as processing (Clement et al 1999). For this species, tissue culture techniques are considered to be the most efficient strategy for clonal plantlet regeneration, as well as for genetic conservation (Mora-Urpí et al 1997), although a commercial protocol does not currently exist.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit is an excellent food, with starches, lipids, carotene and all essential amino acids (Yuyama et al 2003). The heart-of-palm is composed of unexpanded juvenile leaves and subapical tissue, and has low concentrations of peroxidases and polyphenoloxidase, allowing in natura commercialization, as well as processing (Clement et al 1999). For this species, tissue culture techniques are considered to be the most efficient strategy for clonal plantlet regeneration, as well as for genetic conservation (Mora-Urpí et al 1997), although a commercial protocol does not currently exist.…”
Section: Introductionmentioning
confidence: 99%
“…Valentini (2010) characterized the peach palm heart-of-palm produced at different times of harvest and observed that the pH value ranged from 6.14 to 6.33, and the soluble solids from 8.3 to 6.2° Brix. Clement, Santos, and Andrade (1999) observed a shelf life of 14 days in minimally processed peach palms in the form of stick, when stored at 10°C. Fonseca et al (2019) evaluated the physicochemical properties of peach palm heartfor minimal processing, and found 8.6° Brix mean soluble solids values and 6.5 pH for median region heart-of-palm, stick type cut, and 7.4° Brix and 6.3 pH for the basal part, chopped type cut.…”
Section: Quality Of Peach Palm Heart Minimally Processedmentioning
confidence: 97%
“…** Por valor exportado 4 *** AtéAgo/2006 No mercado de exportação, o palmito de pupunha está substituindo os do gênero Euterpe devido à melhor qualidade, menor preço e à expansão da produção na América Tropical. Porém, o mercado internacional está se expandindo lentamente, provavelmente por causa da baixa qualidade do produto enlatado das palmeiras açaí e juçara(CLEMENT et al, 1999).De acordo com Mora-Urpí et al (1991), as principais causas do mercado internacional (principalmente nos…”
unclassified